Fabrication of Well-Aligned TiO2 Nanotube Arrays with Outstanding Light-Induced Hydrophilicity Performance. Issue 14 (1st January 2016) - Zhang, Miao; Sun, Zhaoqi; Cao, Chunbin; He, Gang; Lv, Jianguo; Wang, Peihong; Yang, Lei; Ding, Zongling; Gong, Zezhou; Tao, Jiajia; Wang, Xingzhi; Wang, Zhuang
Abstract : TiO2 nanotube arrays (TiO2 -NTAs) were respectively fabricated using traditional one-step oxidation and re-oxidation method on a titanium surface in fluorine-containing electrolytes. Microstructures, optical properties of specimen were characterized by X-ray diffractometer, digital microscope, field-emission scanning electron microscope and ultraviolet-visible spectroscope. Compared with the one-step oxidation, the resulted samples showed more uniform surface, longer tube length and statistical higher absorption in visible light region. Importantly, a new growth mechanism named template-induced growth model is proposed to explain the growth of TiO2 -NTAs prepared by re-oxidation approach in present work. Besides, water contact angles of samples before and after irradiated by UV light were measured and discussed in detail. It is confirmed that samples obtained from re-oxidation method have more hydroxyl groups can be formed when irradiated by UV light, which lead to more sensitive light-induced hydrophilicity finally. The light-induced hydrophilic performance of TiO2 -NTAs would be favorable to improve the likelihood of electrolyte contacting of the surface, which is useful in many realistic application instances.